Design and Fabrication of Electric Foldable Bike - Mr. Akshay Talekar (International Journal for Research in Applied Science and Engineering Technology, 2022)
Abstract: In the current lifestyle, man isn't able to dedicate specific time for his health. This importance towards exercise and body fitness thanks to time shortage and stressful life is extremely low. To address the time deficit, we are able to utilize the time spent on commuting efficiently to exercise by using bielectric bikes, thereby also contributing to pollution control. But regular bielectric bikes occupy sufficient space to park and aren't easy to hold around additionally because of the possibility of theft. Transport has been one of the foremost important issues to be restricted within the present day situation, as commuting from place to position within the town has become a tedious and a chic task. it's very difficult to succeed in the closest transport facility and in many cases the destination is very far away from most roads where the general public transport won't be able to commute or it'd be very expensive. To overcome a typical problem faced by the society, a plan is conceptualized International Journal for Research in Applied Science & Engineering Technology (IJRASET) ISSN: 2321-9653; IC Value: 45.98; SJ Impact Factor: 7.538 Volume 10 Issue V May 2022- Available at www.ijraset.com ©IJRASET: All Rights are Reserved | SJ Impact Factor 7.538 | ISRA Journal Impact Factor 7.894 | 5330 to style and fabricate a foldable bielectric bike. We have already seen many foldable bielectric bikes within the global market but the main idea of this project is to supply a foldable bielectric bike which is light & sleek yet rigid & safe. It's easy to handle and straightforward to take care of. Unlike the standard electric bikes, this bielectric bike will occupy very less space and is also very easy to hold around. Also it utilises the regenerative braking system. The most objective is to style and develop a foldable bielectric bike which is comfortable to ride and economical